2012
DOI: 10.4103/0971-6580.103678
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to petroleum hydrocarbon: Implications in lung lipid peroxidation and antioxidant defense system in rat

Abstract: Objective:Various studies have implicated automobile exhausts as risk factors in cardiovascular and pulmonary diseases; however, there is little or no documentation on the role of the main source of the exhausts, petroleum hydrocarbons, on cardiopulmonary pathologies. Thus, we investigated the effect of petroleum hydrocarbons, using various petroleum products, on histomorphology of the lung and the role of lipid peroxidation in it.Materials and Methods:Control rats were not exposed to any of the petroleum prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…The severe bacterial pneumonias found in UME dolphins could represent a chronic sequelae to hydrocarbon inhalation or aspiration, or have been secondary to PAH induced immune system compromise. The most common sequela to hydrocarbon inhalation and ingestion in humans and animals are aspiration pneumonia and pneumonia often involving the bronchioles [ 64 – 68 ]. Inhaled hydrocarbon vapors or aspirated hydrocarbons may cause necrosis of bronchial and bronchiolar epithelium, and pneumocyte and alveolar septal necrosis which leads to inflammation and secondary infection [ 64 – 66 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The severe bacterial pneumonias found in UME dolphins could represent a chronic sequelae to hydrocarbon inhalation or aspiration, or have been secondary to PAH induced immune system compromise. The most common sequela to hydrocarbon inhalation and ingestion in humans and animals are aspiration pneumonia and pneumonia often involving the bronchioles [ 64 – 68 ]. Inhaled hydrocarbon vapors or aspirated hydrocarbons may cause necrosis of bronchial and bronchiolar epithelium, and pneumocyte and alveolar septal necrosis which leads to inflammation and secondary infection [ 64 – 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…The most common sequela to hydrocarbon inhalation and ingestion in humans and animals are aspiration pneumonia and pneumonia often involving the bronchioles [ 64 – 68 ]. Inhaled hydrocarbon vapors or aspirated hydrocarbons may cause necrosis of bronchial and bronchiolar epithelium, and pneumocyte and alveolar septal necrosis which leads to inflammation and secondary infection [ 64 – 66 ]. During the 2007 firestorm in San Diego, dolphins and people living in San Diego Bay area were exposed to high levels of PAHs [ 69 , 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…Markers of oxidative stress, neutrophil inflammation, and enzymatic antioxidants were assayed using standardized enzymatic colorimetric method with assay kit as previously documented in our studies [ 13 , 27 , 28 , 29 , 30 ]. Briefly, MDA, the marker of lipid peroxidation, was measured as the amount of thiobarbituric acid reactive substance, TBARS, generated during lipid peroxidation.…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, vascular toxicity may be indicated by a combustion emission component [50]. Inhaling petroleum hydrocarbons has been linked by Azeez et al [51] to the development of oxidative stress, which may be a risk factor in the pathogenesis of pulmonary dysfunction. Hallare [52] also suggested that workers at petrol stations and law enforcement agencies are more likely to suffer chromosomal damage due to exposure to potential genotoxic gaseous and particulate pollutants from internal combustion engines utilised in cars.…”
Section: Discussionmentioning
confidence: 99%